2018
DOI: 10.1126/science.aaj1853
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD4 T cell memory by local cellular collectivity

Abstract: Cell differentiation is directed by signals driving progenitors into specialized cell types. This process can involve collective decision-making, when differentiating cells determine their lineage choice by interacting with each other. We used live-cell imaging in microwell arrays to study collective processes affecting differentiation of naïve CD4 T cells into memory precursors. We found that differentiation of precursor memory T cells sharply increases above a threshold number of locally interacting cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 52 publications
6
73
0
Order By: Relevance
“…Another recent study suggested that early IL-2 produced by nascent Tfh/T CM precursors signaled in a paracrine manner to CD25 hi counterparts, which supported Th1 differentiation. 25 This study raises the possibility that local signals mediated by IL-2 between adjacent CD4 + T cells can influence fate, a theme explored in vitro by Polonsky et al 26 In that study, IL-2 produced by a quorum of neighboring CD4 + T cells triggered the expression of CD62L, employed as a marker of T CM cells. 26 These findings appear to sit at odds with a model in which IL-2 signaling supports effector CD4 + T cells and T EM cells, not T CM cells.…”
Section: Controlling the Development Of Cd4 + T-cell Memorymentioning
confidence: 86%
“…Another recent study suggested that early IL-2 produced by nascent Tfh/T CM precursors signaled in a paracrine manner to CD25 hi counterparts, which supported Th1 differentiation. 25 This study raises the possibility that local signals mediated by IL-2 between adjacent CD4 + T cells can influence fate, a theme explored in vitro by Polonsky et al 26 In that study, IL-2 produced by a quorum of neighboring CD4 + T cells triggered the expression of CD62L, employed as a marker of T CM cells. 26 These findings appear to sit at odds with a model in which IL-2 signaling supports effector CD4 + T cells and T EM cells, not T CM cells.…”
Section: Controlling the Development Of Cd4 + T-cell Memorymentioning
confidence: 86%
“…N prod > 1, 000. This estimate illustrates that there exist thresholds of activation for immune responses, whereby the systems needs a critical mass of activated, cytokinesecreting cells to overcome consumption and drive activation and differentiation [86]. The estimate above does not take into account some of the intricacies of IL-2 regulation: positive feedback in IL-2 secretion, recycling of IL2Rα chains, upregulation of IL-2R in T reg cells have been documented.…”
Section: Regulation By Cytokine Consumptionmentioning
confidence: 96%
“…Recent experiments have revisited the question of naive T-cells differentiation into different memory cell types upon antigen stimulation, by considering collective effects through cell-cell communication. Polonsky et al [86] tracked live cells tagged with antibody markers over time in microwells with different initial cell numbers. By continuously tracking individual cell differentiation states and proliferation, they are able to overcome the limitations of bulk experiments where local cell densities are hard to control.…”
Section: Quorum Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…to the progenitor-exhausted state (Miller et al, 2019) and to the tuning of the critical number of T cells 82 required for proper differentiation (Polonsky et al, 2018). 83…”
mentioning
confidence: 99%